Optimum distributed generation allocation using modified particle swarm optimization - Sahib, Taha Jabbar (2017)
The expansion of the Distribution Generation (DG) is consistent with its increasing popularity as a sustainable part of electric power systems. DG, being small scale generation sources placed either at or near the load centre, is normally installed in the power system network. DG optimum allocation brings a number of positive impacts- voltage improvement, environmental friendliness, delay in the system upgrade, more reliable and reduced transmission and distribution network congestion, also lower network upgrading cost are the positive points of DG integration to the system. The integration of DG into distribution might be caused several issues such as voltage rise and power losses increment. In this dissertation, the voltage improvement and power losses reduction have become the main objective of this study. The impact brought on by the DG is positive or negative on the system, depending mostly on the DG location and size. The optimal allocation of DG has been considered as main problem that can be solved using Modified Particle Swarm Optimization (MPSO) method. This dissertation has the aim of developing a successful technique that can assess the consequence of distributed generation on a distribution power system and to adopt the MPSO technique to find DG units optimal placement and size with improved system reliability by mitigating the total power losses, and improving the voltage profile. This dissertation also use the Open Distribution System Simulator (OpenDSS) and MATLAB. The MPSO technique solved the optimal DG sizing and placement problem for the IEEE 13-Node, 37-Node and 123-Node Test Cases successfully. Each case is divided into three scenarios and each scenario deals with different constraints for the size and number of DG to integrate with the test case. The test cases and its scenarios have been utilized to show the effectiveness of the MPSO method to find the optimum DG allocation and demonstrate how this optimum DG allocation makes the voltage profile better and minimizes the total power losses of the test cases study.